Analisis Karakteristik Curah Hujan di Kota Banjarbaru Berdasarkan Data Stasiun Klimatologi Banjarbaru - Elma Sofia; Maya Amalia (Jurnal Teknologi Berkelanjutan, 2021)
The characteristics of rainfall in Banjarbaru City can be known by analyzing rainfall data in Banjarbaru City. This rainfall analysis uses data from the Banjarbaru climatology station. By analyzing the characteristics of the rainfall in Banjarbaru City, it is expected to provide an overview of cropping patterns and estimation ofthe planting period. The resulting information is expected to help farmers anticipate and estimate and adjust crop planting schedules according to the climate during wet and dry months. In addition, from the calculation of the intensity of rainfall, the IDF curve will also be obtained, which can be a reference for calculating the planned flood discharge.